Significant Stability Enhancement in High‐Efficiency Polymer:Fullerene Bulk Heterojunction Solar Cells by Blocking Ultraviolet Photons from Solar Light. Issue 4 (17th November 2015) - Jeong, Jaehoon; Seo, Jooyeok; Nam, Sungho; Han, Hyemi; Kim, Hwajeong; Anthopoulos, Thomas D.; Bradley, Donal D. C.; Kim, Youngkyoo
Abstract : Achievement of extremely high stability for inverted‐type polymer:fullerene solar cells is reported, which have bulk heterojunction (BHJ) layers consisting of poly[4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithiophene‐alt‐3‐fluorothieno[3, 4‐b]thiophene‐2‐carboxylate] (PTB7‐Th) and [6, 6]‐phenyl‐C71‐butyric acid methyl ester (PC71 BM), by employing UV‐cut filter (UCF) that is mounted on the front of glass substrates. The UCF can block most of UV photons below 403 nm at the expense of ≈20% reduction in the total intensity of solar light. Results show that the PTB7‐Th:PC71 BM solar cell with UCF exhibits extremely slow decay in power conversion efficiency (PCE) but a rapidly decayed PCE is measured for the device without UCF. The poor device stability without UCF is ascribed to the oxidative degradation of constituent materials in the BHJ layers, which give rise to the formation of PC71 BM aggregates, as measured with high resolution and scanning transmission electron microscopy and X‐ray photoelectron spectroscopy. The device stability cannot be improved by simply inserting poly(ethylene imine) (PEI) interfacial layer without UCF, whereas the lifetime of the PEI‐inserted PTB7‐Th:PC71 BM solar cells is significantly enhanced when UCF is attached. Abstract : The stability of inverted‐type polymer:fullerene solar cells with PTB7‐Th:PC71 BM bulk heterojunction layers is shown to be significantly improved by employing a UV‐cut filter, which blocks UV photons that trigger degradation of organic materials in the bulk heterojunction layers.